Current and future perspectives on the regulation and functions of miR-545 in cancer development - Shen, Jinze; Su, Xinming; Wang, Qurui; Ke, Yufei; Zheng, Tianyu; Mao, Yunan; Wang, Zehua; Dong, Jingyin; Duan, Shiwei (Cancer pathogenesis and therapy, 2024)
Micro ribonucleic acids (miRNAs) are a highly conserved class of single-stranded non-coding RNAs. Within the miR-545/374a cluster, miR-545 resides in the intron of the long non-coding RNA (lncRNA) FTX on Xq13.2. The precursor form, pre-miR-545, is cleaved to generate two mature miRNAs, miR-545-3p and miR-545-5p. Remarkably, these two miRNAs exhibit distinct aberrant expression patterns in different cancers; however, their expression in colorectal cancer remains controversial. Notably, miR-545-3p is affected by 15 circular RNAs (circRNAs) and 10 long non-coding RNAs (lncRNAs), and it targets 27 protein-coding genes (PCGs) that participate in the regulation of four signaling pathways. In contrast, miR-545-5p is regulated by one circRNA and five lncRNAs, it targets six PCGs and contributes to the regulation of one signaling pathway. Both miR-545-3p and miR-545-5p affect crucial cellular behaviors, including cell cycle, proliferation, apoptosis, epithelial-mesenchymal transition, invasion, and migration. Although low miR-545-3p expression is associated with poor prognosis in three cancer types, studies on miR-545-5p are yet to be reported. miR-545-3p operates within a diverse range of regulatory networks, thereby augmenting the efficacy of cancer chemotherapy, radiotherapy, and immunotherapy. Conversely, miR-545-5p enhances immunotherapy efficacy by inhibiting T-cell immunoglobulin and mucin-domain containing-3 (TIM-3) expression. In summary, miR-545 holds immense potential as a cancer biomarker and therapeutic target. The aberrant expression and regulatory mechanisms of miR-545 in cancer warrant further investigation. [Display omitted] •Abnormal microRNA (miR)-545 expression is observed in cells, tissues, and serum across different cancer types.•miR-545 faces competitive inhibition from 12 circular RNAs and 11 long non-coding RNAs, regulating 40 downstream genes.•miR-545 modulates five key pathways and various cellular biological behaviors.•miR-545 substantially affects cancer cell sensitivity to radiation and chemotherapy.•miR-545 modulates immune cell infiltration levels and shows implications in immunotherapy.